HUBUNGAN PERAN PEER EDUCATOR PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) DENGAN PERUBAHAN PERILAKU KESEHATAN REPRODUKSI REMAJA - RAIVI, AAN; Kuntoro, Kuntoro; Rukmini devy, Srimarti (Poltekkes Kemenkes Banjarmasin, 2015)
Introduction: Adolescent is a period of transition that must be passed all childhood to adulthood. Many things happen in this phase, adolescents who successfully passed the transition phase will determine the success undergo adult stage. This study focuses on one issue, namely the adolescentreproductive health triad as adolescent sexuality, premarital sexual behavior resulting in the risk of unwanted pregnancy. Causes of adolescent premarital sex because of the lack of knowledge of adolescent reproductive health in SMAN 1 Arjasa (79.6%).Taboo of sex education to students area needs communication, information, and education with true, appropriate, and effective that peer educator with simultaneous for the studens area and important to reproduction health information, early marriage and risk it, premarital sexual and risk it for communication, information, and education in integral to tackling early marriage happened. Purpose: The purpose of this study was to analyze the relationship of peer educatorsrole Youth Information and Counseling Center to behavior change of adolescent reproductive health. Methods: This study was an experimental study, the type of study design pre experiment one group pretest posttest design. Technique sampling is total sampling. The population in this study were 622 students with a sample of 208 students in secondclass SMAN 1 Arjasa. Results: Data analysis was performed using Wilcoxon signed rank test test with significance level of p Ë Î± = 0:05. Results from this study is p value of 0.010 with Î± = 0.05%, and p value of 0.000 with Î± = 0.05%. The meaning of there are relationship of peer educators role Youth Information and Counseling Center to behavior change of adolescent reproductive health. Discussion : knowledge and adolescent after be done health education by peer educator happen to increase of knowledge and adolescent attitude about reproduction health become good. Conclusions: knowledge, attitudes, and behavior effected to peer educator.Keywords: Â Peer Educator, PIK-R, behavior change, adolescent reproductive Â Â Â Â Â Â Â health